PERKEMBANGAN JUMLAH PENDUDUK DAN LUAS LAHAN PERTANIAN DI KABUPATEN MINAHASA SELATAN - Yoan F. A. Tulenan; Paulus Pangemanan; Grace A. J. Rumagit; Ellen G. Tangkere (Universitas Sam Ratulangi, 2014)
ABSTRACTOne of the problems in South Minahasa Regency is the reduction of the agricultural land area, which is caused by the increasing number of residents. This is caused by conversion of the agricultural land. The objective of this research is to analyze the growth of the number of the population and agricultural land area and analyze the relation between of the number population and agricultural land area in South Minahasa Regency.This research uses primary and secondary data. The Primary data in this research were obtained from the result of direct interview with the Department of Agriculture and Livestock of South Minahasa, Department of Population and Civil Registration of South Minahasa, Forestry Department of South Minahasa, and the South Minahasa community leaders. The secondary data of thus research were obtained from the Central Statistics Agency of North Sulawesi and the Central Statistic Agency of South Minahasa. This research uses trend analysis and correlation analysis which was supported by qualitative approach.This research result showed that the number of population increases up to year 2020 and the agricultural land area in South Minahasa decreases up to year 2020. Based on this research, it could be concluded that the total population has a close relation with an area of agricultural land caused the increasing of the number of the population caused the decreasing of the agricultural land area due to the conversion of function of agricultural land to non agricultural land.